Writing Poetry with the Development of Associative Meaning in Chairil Anwar's Poetry Collection: A Lesson of Poetry Writing Instruction - Firmansyah, Bagas Eko; Amilia, Fitri; Anggraeni, Astri Widyaruli (Journal of Language and Literature Studies, 2025)
This research is motivated by the importance of associative meaning in poetry as a formative element of imaginative power, emotion, and linguistic creativity. However, there has been limited research systematizing associative meaning techniques as a model for poetry writing instruction. This study aims to analyze associative meaning techniques in Chairil Anwar's poems and formulate their implications for poetry writing instruction. This research employs a qualitative descriptive design with semantic analysis of eight selected poems from the collection Aku Ini Binatang Jalang (I Am a Wild Animal). Data were collected through repeated reading and note-taking techniques, while data analysis was conducted through componential analysis, referential analysis, and meaning verification using KBBI (the Indonesian Dictionary). The research findings indicate that there are three dominant techniques in the development of associative meaning in Chairil Anwar's poetry: meaning components, rewriting, and synonymy. The synonymy technique is the most frequently used, followed by rewriting and meaning components. These findings demonstrate that associative meaning plays a crucial role in strengthening the expressive power and semantic depth of poetry. These findings have implications for poetry writing instruction, namely the need for explicit teaching of associative techniques to help students enrich their diction choices and expand semantic creativity in their poetic works.